Characteristic of Chicken Liver Nuggets Using Different Types of Flour as Fillers - Amertaningtyas, Dedes; Ramadhan, Januar Fajrul; Evanuarini, Herly; Andriani, Ria Dewi (Journal of Agriprecision & Social Impact, 2025)
Chicken liver is rich in protein and iron, which can help prevent anemia and stunting. One innovation is processing chicken liver into nuggets, a popular ready-to-eat food product. This study aims to explore the effects of various flours (cornstarch, soybean, pumpkin, and carrot) on the characteristics of chicken liver nuggets, including yield, texture, water activity, moisture content, and color. By utilizing nutrient-dense flours, it is hoped that chicken liver nuggets can become more nutritious, healthier, and meet quality standards, while also holding the potential for commercialization on both household and large-scale industries, supporting community food security. This research employed a Completely Randomized Design (CRD) with four treatments and three replications. The tested variables included yield, water activity (Aw), water content, texture, and color. The analysis results indicated that the treatments had a highly significant effect (P>0.1) on yield and color, a significant effect on moisture content, and no significant effect on texture and water activity. The findings revealed that chicken liver nuggets had average yield values of 96.38%-103.27%, texture of 4.094 N-5.236 N, Aw of 0.857-0.870, moisture content of 33.70%-42.04%, and color values of L* (lightness) 36.90-43.27, a* (redness) 12.67-16.77, and b* (yellowness) 19.17-22.23. This study demonstrates that the use of cornstarch, soybean, pumpkin, and carrot flours can improve the quality of chicken liver nuggets, making them suitable for consumption as a menu variation with quality that complies with the Indonesian National Standard (SNI) for chicken nuggets with additives.